Variation of Mechanical Properties of Cr Doped Bi-2212 Superconductors - Doğruer, Musa; Yıldırım, Gürcan; Öztürk, Özgür; Belenli, İbrahim; Terzioğlu, Cabir (Springer Science and Business Media LLC, 2013)
This study shows the influence of Cr inclusions on the mechanical properties of Bi1.8Sr2.0Cr x Ca1.1Cu2.1O y (Bi-2212) superconducting samples (x=0, 0.1, 0.3, 0.5, 0.7, and 1) prepared by conventional solid-state reaction route with the aid of the microhardness (H v) measurements. Moreover, some characteristics such as Vickers microhardness, Young’s (elastic) modulus (E) and yield strength (Y), being responsible for the potential technological and industrial applications, are theoretically evaluated from the microhardness curves belonging to the samples and compared with each other. It is found that the load dependent microhardness values decrease nonlinearly as the applied load enhances until 2 N beyond, which the curves shift to the saturation region, confirming that all the samples exhibit the indentation size effect (ISE) nature. Further, the elastic modulus and yield strength values observed reduce with the enhancement of the applied load and Cr inclusions in the Bi-2212 matrix. The experimental findings are also analyzed by Meyer’s law, proportional sample resistance model (PSR), modified proportional sample resistance model (MPRS), elastic/plastic deformation model (EPD), and Hays–Kendall (HK) approach. According to the results obtained, the load independent microhardness values calculated by EPD, PSR, and MPSR models are far from the values of the plateau region; however, the HK approach is the most suitable model for the microhardness calculations of the samples prepared in this study.
Keywords: H-EPD; H-MPSR; H-HK; Bi1.8Sr2.0CrxCa1.1Cu2.1Oy; H-PSR; H-v